Influence of Chromium and Cobalt Doping On Structural Properties and Magnetic Imaging of Nd 0.75 Na 0.25 Mn 1-x Cr x O 3 and Nd 0.75 Na 0.25 Mn 1-y Co y O 3 - Ahmad Mustaqim Bin A.Halim; Suhadir Bin Shamsuddin (Enhanced Knowledge in Sciences and Technology, 2022)
The effect of chromium and cobalt doped at Mn site of perovskite manganite Nd 0.75 Na 0.25 Mn 1-x Cr x O 3 (x= 0, 0.02, and 0.05) and Nd 0.75 Na 0.25 Mn 1-y Co y O 3 (y=0.0.2 and 0.05) have been investigated to compare crystalline phase. A solid state reaction method was used to prepare the sample with a high purity oxide powder and were characterised by using X-ray Diffractometer to studied its lattice parameter. Another analysis done using atomic force microscope to get the magnetic topology of the samples. The XRD measurement has showed the samples are crystallised in a single phase in orthorhombic structure with a space group of Pnma. In comparison with the chromium and cobalt, Co 3+ ion has a larger ionic radius than Cr 3+ , therefore affecting the unit cell volume (V). The spectral RMS amplitude reading in magnetic topology of Nd 0.75 Na 0.25 Mn 1-x Cr x O 3 (x= 0, 0.02, and 0.05) and Nd 0.75 Na 0.25 Mn 1-y Co y O 3 (y= 0.0.2 and 0.05) revealed a different number of readings. It can be observed that the magnetic topology pattern of Cr in a close pattern. The spectral RMS amplitude for Cr also larger than Co. In conclusion, this research has succeeded to detect the crystalline phase for all the samples and determine its lattice parameter with the unit cell volume. For magnetic topology, we manage to detect the spectral RMS amplitude for chromium and cobalt doped in Mn site and compare its structure.